A vision-based dual-modal system for adjusting the orientation and plant spacing of ginger with biharmonic depth completion and rapid hand–eye calibration - Shuxiang He; Lin Liu; Yihe Zhang; Jin Cheng; Yuhua Li; Jialin Hou; Rui Hou; Kai Zhou (Computers and Electronics in Agriculture, 2026)

Structure-resistant chlorophyll index: A novel indicator for leaf chlorophyll content monitoring - Si Gao; Kai Yan; Jinhua Li; Cheng Huang; Xuanlong Ma; Wenjie Fan; Liangyun Liu; Qiao Wang (Remote Sensing of Environment, 2026)

Vertical aerosol profiles and the impact of regional transport in a background region of Northwest China: Insights from ground-based lidar - Kai Cheng; Xia Li; Yaqiong Kuang; Yuting Zhong; Haiyang Cai; Shuting Li (Atmospheric Research, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

Stable acid-responsive two-component lipid vesicles for redox regulation-enabled ferroptosis-driven immunotherapy of hepatocellular carcinoma - Chengyuan Cai; Jing Wen; Xiao Wang; Zike Liao; Jinmei Cheng; Jiaxin Li; Jisheng Xiao; Zhong-Kai Cui; Xiaopin Duan (Chemical Engineering Journal, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

SERS sensing platform based on MIL-100(Fe)@AgNPs for norepinephrine/adenosine monitoring in patient plasma - Peng Zhao; Kai Liu; Yueyan Li; Xiaofang Ban; Yuheng Wu; Jiaqi Liu; Xiaohong Wu; Ziyi Cheng; Fan Wang; Shuo Li; Feng Lin; Huifang Tang; et al. (Analytica Chimica Acta, 2026)

Synergistic analysis and vertical transport attribution of carbon monoxide surface concentrations and satellite column loadings over China - Shuo Wang; Jason Blake Cohen; Kai Qin; Luoyao Guan; Pravash Tiwari; Ye Feng; Xiaolu Li; Qin He; Zhengqiang Li; Cheng Fan; Dacheng Wang (Remote Sensing of Environment, 2026)

Comparative evaluation of bio-additives for promoting typical PPCPs degradation and reducing ecological risk during sewage sludge composting - Jishao Jiang; Yanbin Huang; Zhuyu Tang; Kai Liu; Shipeng Wang; Yunbei Li; Jinghua Lv; Chunyan Zhang; Dong Liu; Parag Bhople; Ke Cheng (Journal of Environmental Chemical Engineering, 2026)

Synergistic separation and degradation of pollutants using novel self-cleaning catalytic membrane by coupling of heterogeneous fenton and membrane distillation - Guowei Zhang; Jie Li; Xiaoping Jiang; Danya Mei; Danni Ding; Xuelian Xiong; Kai Cheng; Qian Li (Journal of Environmental Chemical Engineering, 2026)

A programmed magnetic resonance tuning probe for tumor miRNA-21 imaging and drug release monitoring - Minghui Chen; Xueqi Li; Zhen Zhang; Hao Zhang; Xingyu Chen; Jiali Wang; Kai Xu; Guohui Cheng (Chemical Engineering Journal, 2026)

Indium selenide framework constructed from supertetrahedral clusters for efficient adsorption of Cs+ and Sr2+ - Fei-Fei Wang; Yu-Hang Li; Ze-Jia Shen; Ze-Yu Wang; Lin Cheng; Shuaihua Wang; Kai-Yao Wang (Chemical Engineering Journal, 2026)

Forchlorfenuron (CPPU) suppresses fruitlet abscission in Areca catechu by modulating carbohydrate allocation, hormonal dynamics, and lignin biosynthesis - Lin-Kai Wang; Wen-Cheng Fan; Han Gong; Dong-Xia Li; Li-Yun Liu; Meng Li; Jia Li (Planta, 2026)

Effects of boundary on vapor–liquid flow characteristics in tube bundle - Yawen Wang; Wenchu Niu; Defei Chen; Kai Xu; Chang Zeng; Wei Li; Jianjie Cheng (Annals of Nuclear Energy, 2026)

Matrine ameliorated myocardial ischemia-reperfusion injury through lipid accumulation reduction by activating JAK2-STAT3-CPT1 signaling pathway - Mengyan Liu; Xin Cheng; Huan Jiang; Yuna Mao; Jianbin Li; Chuncan Qiao; Xiaoyu Wang; Wanrong Wang; Shan Gao; Kai Zhou (Toxicology and Applied Pharmacology, 2026)

Polystyrene nanoplastics perturb cell membranes and induce bystander uptake of diverse cargos - Tao Wang; Yang Yan; Tinghao Xu; Xiangyang Li; Cheng Xu; Yushuang Wei; Hong Liu; Kai Yang; Bing Yuan (Journal of Hazardous Materials, 2026)

El Niño-Southern oscillation frequency influences the composition of evergreen and deciduous broadleaved mixed forests in southwestern China since the mid–Holocene - Zimeng Guo; Xiao Zhang; Kai Li; Mengna Liao; Lina Liu; Haiyan Li; Jun Cheng; Jian Ni (Global and Planetary Change, 2026)

Oral sunflower pollen-derived biomimetic delivery system for combined chemoimmunotherapy of colorectal cancer - Xin-Yue Xu; Meng Guan; Kai Cheng; Yong-Guo Hu; Li-Li Chen; Zi-Hui Yan; Jie Xiong; Dong Zhou; Jia-Hua Zou; Jin-Xuan Fan; Yuan-Di Zhao; Xiao-Shuai Zhang (Chemical Engineering Journal, 2026)

An integrated in-situ coordination strategy enabling high-performance layered cathodes for sodium-ion batteries - Hongyi Wang; Zixuan Huang; Craig A. Bridges; Cheng Li; Zhi Long; Shilong Li; Kai Liu; Shiqiang Liu; Qingqing Zhang; Sung-Soo Kim; Xiao-Guang Sun; Lianqi Zhang; et al. (Chemical Engineering Journal, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Magnetic MnFe2O4 modified sludge biochar for peroxymonosulfate activation to enhance deep dewatering of excess sludge: Performance and synergistic mechanism - Jinyun Guan; Kai Cheng; Cong Zhang; Yihang Sun; Yichenyang Li; Chong Li; Jifeng Guo (Process Safety and Environmental Protection, 2026)

Post-scour reliability assessment of offshore monopiles incorporating field monitoring data and multivariate Gaussian modelling - Yuting Zhang; Kai Wen; Qiang Li; Xinglei Cheng; Haoran Ouyang; Jiawei Xie; Yanhao Zheng (Ocean Engineering, 2026)

Exogenous calcium modulates oxalic acid metabolism via repression of LcAAE3 and mediates calcium accumulation in litchi pericarp and fruit pedicel - Dong-Cheng Li; Zhi-Qun Zhong; Teng-Kai Chen; Yi-Tong Liu; Yue-Han Sun; Hui-Cong Wang; Ren-Fang Zeng; Xu-Ming Huang (Journal of Plant Physiology, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Elucidating functional group governance for catalytic synthesis of bio-based aromatic amines - Ge-liang Xie; Yu Luo; Kai-cheng Xia; Sheng-ren Li; Lujiang Xu; Zhen Fang (Biomass and Bioenergy, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Agent-specific bleeding signatures in non-hypertensive versus hypertensive patients exposed to oral anticoagulants: a real-world pharmacovigilance study - Ying Feng; Hua-Hua Liu; Liu-Cheng Li; Kai-Li Mao; Xiao-Fang Niu; Jie Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

First record of Fraxinoxylon (Oleaceae) from the Miocene of Sihong, Jiangsu Province, China, and its palaeogeographic implication - Yanbin Zhu; Ya Li; Xiaohua Zhou; Yanfeng Song; Kai Liu; Ren Jiang; Yeming Cheng (Review of Palaeobotany and Palynology, 2026)

Convergent shifts in microbial communities: Petroleum hydrocarbon contamination suppresses matrix heterogeneity - Wenjuan Jia; Jingcheng Li; Kai Wang; Lirong Cheng; Naifu Jin; Qing Yang; Dan Zhang; Xuefeng Xia; Nuchao Xu; Mingming Wang; Jin Meng; Yi Zhu; et al. (Journal of Hazardous Materials, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Dynamic and residual static performance of steel beam-column subframes with extended end-plate connections under elevated temperatures - Kai Qian; Quan Luo; Zhi Li; Xi Lan; De-Cheng Feng (Engineering Structures, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

Ecosystem-scale energy balance characteristics in mixed coniferous and broad-leaved forests in southwestern China - Kun Zhao; Yunqi Wang; Lei Ma; Cheng Li; Kai Wang; Xuanwo Liu; Shuting Gong; Xiaodong Niu; Yonglin Zheng; Chuan Jin (Agricultural and Forest Meteorology, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Hydrodynamic modeling and simulation of a fully appended AUV with X semi-dynamic rudder in complex wave conditions near the free surface - Kai Zhang; Liang Cheng; Qing Wang; Weifeng Yang; Jiangxiong Li; Yinglin Ke (Ocean Engineering, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Plasma assisted electrospinning technology for functional food packaging: Strategies, applications, and prospects - Kai Zhang; Zichen Li; Jun-Hu Cheng (Food Packaging and Shelf Life, 2026)

Fluorine functionalized MIL-101 endows polymer electrolyte with highly Li+ dissociation, Li+ transference number and stabilized SEI for high-rate lithium metal batteries - Kai Liu; Ziying Liu; Kaixiang Zhi; Chang Liu; Huarui Zhang; Zhenyuan Hu; Yunfeng Zhang; Fan Xia; Chen Li; Hansong Cheng (Chemical Engineering Journal, 2026)

Ultrahigh-holmium carbon dots enable single-element-mediated dual-modality CT/MR imaging in vivo - Nan Liu; Ke Xiang; Tiantian Guo; Shuo Li; Qiyu Sun; Jinbin Pan; Ran Cheng; Dingbin Liu; Cai Zhang; Gang Shu; Shao-Kai Sun (Chemical Engineering Journal, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Genetic mapping and identification of a major quantitative trait locus associated with the high fiber strength introgressed from Gossypium barbadense - Kai Wang; Haohong Tang; Cong Sun; Xiaohu Ma; Shen Ren; Jie Li; Xinyu Zhang; Shuaishuai Cheng; Xianpeng Xiong; Jie Sun (Plant Cell Reports, 2026)

Effects of Iodine Nutritional Status on Thyroid Proliferation of SD Rat - Junshuai Cheng; Zifan Gao; Yuan Zhao; Qiuyi Song; Yu Wang; Tingting Xu; Kai Lv; Yanlei Li; Wanqi Zhang; Juan Liu; Long Tan (Biological Trace Element Research, 2026)

Exploring the spatiotemporal variability of leaf area index and its influence on land surface temperature: A city-scale analysis in Hong Kong - Chaoran Zhang; Ran Chen; Xingcheng Lu; Frankie Kwan Kit Wong; Wenkai Li; Kai Cheng; Qin Ma; Yuan Xu; Tung Fung; Qinghua Guo (Urban Forestry & Urban Greening, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

An intelligent ships navigation decision-making method based on multiple navigation intentions and Bayesian game under uncertain conditions - Kai Feng; Xiaoyuan Wang; Jingheng Wang; Junlin Li; Tinglin Chen; Zhenwei Lv; Cheng Shen; Han Zhang; Yabin Li; Yuhan Jiang (Ocean Engineering, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Understanding of a sudden shift from foehn to late spring cold span on the north slope of the Middle Tianshan Mountains with meteorological observation and terrain sensitivity simulation experiments - Maoling Ayitikan; Alaiyi Aiding; Yusufu Musha; Qing He; Chengguang Yang; Wulifan Hanan; Shuting Li; Yuting Zhong; Kai Cheng (Journal of Mountain Science, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Integrated analysis of PM2.5 chemical characteristics and multi-pollutant health risks in Central Taiwan: Implications for optimizing the air quality health index (AQHI) during the COVID-19 pandemic - Po Jui Chen; Tuan Hung Ngo; Shahzada Amani Room; Yuan Cheng Hsu; Yan Cing Li; Shih Yu Pan; Ta Chih Hsiao; Yu-Cheng Chen; Kai Hsien Chi (Science of The Total Environment, 2026)

In situ reactivation of aerobic granular sludge after extended idle conditions: Effect of different N-acyl-homoserine lactones (AHLs) - Long Cheng; Hui Li; Chengyi Luo; Yibo Zhang; Kai Cheng; Siyang Wang; Zhiquan Hu (Journal of Environmental Management, 2026)

Investigation into the impact of cold plasma pretreatment on the pyrolysis reaction characteristics of cellulose - Bin Hu; Guan-Zheng Zhou; Shou-Gang Wei; Zhan-Jun Cheng; Ji Liu; Kai Li; Zhen-Xi Zhang; Qiang Lu (Fuel, 2026)

Proanthocyanidins in food and health: structure–activity relationships, application challenges, and emerging strategies - Ziyu Li; Wenjun Wang; Ping Cheng; Qirong Dong; Haiqi Chen; Kai Fu; Chao Fu; Yunfeng Pu; Donghong Liu (Food Chemistry, 2026)

Seismic Data Reconstruction and Noise Suppression Based on an Improved Weighted Fast Projection onto Convex Sets Algorithm - Gao-peng Cheng; Hua Zhang; Hong-xing Li; Yu Song; Ming Yue; Kai-dong Zhang (Applied Geophysics, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Gram-scale synthesis of ultra-small naked melanin nanoparticles with high aqueous solubility for theranostic applications in vivo - Xingyu Gao; Ruihan Liu; Yao Li; Ran Cheng; Ruxia Liu; Jiaojiao Yu; Xuejun Zhang; Shao-Kai Sun; Quan Zou (Chemical Engineering Journal, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Removal and response mechanisms of sulfamethoxazole in aerobic granular sludge and its molecular interactions with extracellular polymeric substances” [Chem. Eng. J. 528 (2026) 172299] - Long Cheng; Hui Li; Chengyi Luo; Yibo Zhang; Kai Cheng; Siyang Wang; Zhiquan Hu (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

A cross-sectional study of the association between the lymphocyte to high-density lipoprotein ratio and pain in parkinson’s disease - Qiming Jiang; Yanchun Gao; Yuan Yuan; Wanjun Li; Jing Cheng; Jinru Zhang; Xiaoyu Cheng; Kai Li; Junyi Liu; Chengjie Mao (Experimental Brain Research, 2026)

Succession alters carbon cycle regulation by shifting environmental factors and microbial community dominance in arid soils - Xiaonan Li; Kai Zhang; Fengchang Wu; Xiaoli Zhao; Xi Cheng (Applied Soil Ecology, 2026)

A multi-fidelity optimization method applied to asymmetric catenary mooring systems of the FOWT - Zhiyuan Zhao; Xinkuan Yan; Chaozhe Li; Liang Cheng; Kai Wang; Jianhu Fang; Tianhui Fan (Ocean Engineering, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

The biomarker signatures in the Niujiaotang sulfide ore field: Exploring the role of organic matter in ore formation - Yong Cheng; Jia-Xi Zhou; Yuzhao Hu; Saihua Xu; Shengbao Shi; Yiming Wen; Qi Nie; Ye Zhou; Kai Luo; Xiaolin Tan; Liang Zhou; Yadong Li; et al. (Marine and Petroleum Geology, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Real-time prediction and inverse design of multiphase CO2 trapping in deep saline aquifers using machine learning enhanced by SHAP analysis - Shixuan Cheng; Kai Zhang; Yihao Li; Zhangxin Chen (Gas Science and Engineering, 2026)

An update review on plasma-driven polysaccharide degradation: Effects on physicochemical properties, structural characteristics and biological activities - Zhoujie Xu; Xinyao Li; Wen Li; Na Cheng; Kai Li; Zhi Huang (Food Chemistry, 2026)

Effect of freeze-thaw cycles on nitrogen retention in an alpine topsoil amended with peanut shell hydrochar - Yuxi Wu; Jiawen Zhang; Yadi Ai; Weici Quan; Yiwei Gong; Kaiming Yang; Jin Gao; Lu Li; Caiwei Hao; Wenbo Li; Wenjie Ai; Kai Yang; et al. (Environmental Research, 2026)

Removal and response mechanisms of sulfamethoxazole in aerobic granular sludge and its molecular interactions with extracellular polymeric substances - Long Cheng; Hui Li; Chengyi Luo; Yibo Zhang; Kai Cheng; Siyang Wang; Zhiquan Hu (Chemical Engineering Journal, 2026)

Microwave co-pyrolysis of coal slime and sewage sludge: Synergistic mechanism of carbon-oxygen complementation - Lei Ren; Yirou Zhou; Jian Li; Season S. Chen; Kai Zhang; Yanxia Guo; Fangqin Cheng; Jianhua Yan; Lei Wang (Chemical Engineering Journal, 2026)

Chemical composition, source apportionment and formation mechanisms of PM2.5 in urban and background areas of northwestern China - Kai Cheng; Yuting Zhong; Xinchun Liu; Xia Li; Maulen Ayitken; Shuting Li; Hongna Chen; Bingbing Leng; Wang Zhang; Haiyang Cai (Atmospheric Pollution Research, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Synthesis of a hemicyanine-based near-infrared fluorescent probe for the diagnosis of pulmonary fibrosis and acute lung injury - Lu Fan; Yun Guo; Zhen-Zhen Pan; Shuai Ying; Zhong-Yuan Cheng; Kai Wang; Ling Li (Analytica Chimica Acta, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Complexity analysis of navigation situation of intelligent ships in port area with multi-factor coupling - Kai Feng; Junlin Li; Tinglin Chen; Xiaoyuan Wang; Jingheng Wang; Longfei Chen; Quanzheng Wang; Cheng Shen; Yabin Li; Yuhan Jiang (Regional Studies in Marine Science, 2025)

The potential impact of glacier volume changes on biome dynamics in the southeastern margin of the Tibetan Plateau since the last deglaciation - Pengyu Li; Ziru Hao; Yang Yang; Xiao Zhang; Mengna Liao; Lina Liu; Kai Cui; Yongbo Wang; Haiyan Li; Jun Cheng; Kai Li; Jian Ni (Quaternary Science Reviews, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Experimental study of hydrogen release self-ignition at different CH4 ratios - Hao Qi; Zhenmin Luo; Shangyong Zhou; Kai Wang; Tao Wang; Bin Su; Ruikang Li; Fangming Cheng (Fuel, 2025)

Identification of polyester oligomers in laminated steel and their migration into food simulants - Jiaqi Li; Jianing Feng; Changjun Wang; Yifan Cheng; Chunfeng Lv; Canming Li; Kai Qiu; Gang Wu; Yining Xia (Food Packaging and Shelf Life, 2025)

Cigarette butts: A hidden toxic time bomb for aquatic metabolism and behavior - Hairong Lian; Chuhan Xu; Pengrui Xu; Da Tong; Zhizhong Li; Xinfeng Cheng; Kai Zhang; Xianling Xiang (Environmental Pollution, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Composition optimization of ternary Bi-Sn-In alloy anodes for magnesium ion batteries - Zhenhan Li; Kai Zheng; Meijia Song; Tianyi Kou; Xiangyu Fei; Zhenyu Tan; Guanhua Cheng; Zhonghua Zhang (Chemical Engineering Journal, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

Nanozyme taxonomy, mechanistic insights, and controllable synthesis strategies: Advances in precision agricultural applications - Fukai Li; Can Zhou; Jiahao Zhao; Kai Li; Mengrui Yang; Nan Cheng; Lina Qiu; Jian Zhou; Liang Li (Chemical Engineering Journal, 2025)

Estimating the overlooked contribution of adsorption effects on CH4 release in wetland soils using a reactive transport model - Cheng Bei; Peng Liao; Kai Yu; Zhenqing Shi; Rong Li (Journal of Hydrology, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Stimuli-responsive polymeric nanoplatform-mediating immune microenvironment remodeling and noggin silencing for osteogenic regeneration - Yongcan Li; Kaiyuan Cheng; Xinyang Yu; Kai Yang; Jiaqi Lei; Wenjie Zhang; Yangfan Wang; Yunxuan Feng; Shaolong Qi; Jinqun Gan; Zhengwei Mao; Xieyuan Jiang; et al. (Chemical Engineering Journal, 2025)

Photothermal-assisted PMS activation via core-shell FeS2/Bi2MoO6-OVs S-scheme heterojunction for efficient antibiotic degradation and algal inactivation - Jing Li; Dandan Wang; Kai Cheng; Jinyun Guan; Liping Wang; Huan Ma; Lu Zhang; Jifeng Guo (Chemical Engineering Journal, 2025)

Nitrogen-doped hydrothermal carbon as a catalyst for selective alkoxyphenol production from pine pyrolysis - Dong-hong Nan; Cheng-bo Zhang; Qi Niu; Shi-yu Feng; Bin Hu; Ji Liu; Kai Li; Qiang Lu (Biomass and Bioenergy, 2025)

Distribution, partitioning behaviors, and source identification of legacy and emerging per- and polyfluorinated alkyl substances in the Pearl River Estuary, South China - Bin Tang; Can Peng; Dong-Jing Zhou; Kai-Yi Wu; Fei Tian; Hai-Gang Chen; Shi-Yi Zhang; Bo-Wen Li; Guo-Cheng Hu; Ming-Zhong Ren; Jing Zheng (Water Research, 2025)

Metabolic saboteurs: Tire wear particles hijack energy economy of zooplankton - Hairong Lian; Chuhan Xu; Pengrui Xu; Da Tong; Zhizhong Li; Xinfeng Cheng; Kai Zhang; Xianling Xiang (Journal of Hazardous Materials, 2025)

A novel two-stage laccase application strategy to maintain enzyme activity and promote pharmaceuticals and personal care products degradation during sewage sludge composting - Jishao Jiang; Zhuyu Tang; Kai Liu; Shipeng Wang; Yunbei Li; Jinghua Lv; Xu Yan; Dong Liu; Parag Bhople; Ke Cheng (Journal of Environmental Chemical Engineering, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Oxytocin Regulated Neuroinflammation through OTR/Mitochondria Mediated Pathway to Improve Hypoxia-Induced Brain Injury - Xiaomei Yang; Kai Li; Lin Chen; Lei Wang; Xuyang Wang; Kangping Lu; Yu Bai; Yonghao Hou; Jingchen Hou; Chao Wang; Xiaoyan Cheng; Joseph Oldam; et al. (Molecular Neurobiology, 2025)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Molecular docking-based design of novel tricyclic tetrahydropyridothienopyrimidinone derivatives as AChE/MAO-B dual inhibitors - Juan Zhang; Yue Li; Jia-Dong Shao; Guo Wei; Nai-Yu Zhang; Kong-Kai Zhu; Kai-Ming Wang; Cheng-Shi Jiang; Jia-Hong Wang (Molecular Diversity, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Experimental and theoretical investigation on sulfur-doped coal-based hard carbon as anode for sodium-ion batteries - Ansheng Wei; Shanjie Cheng; Kai Yan; Jun Li; Xiao Zhu; Liqiang Zhang; Shouyan Chen (Chemical Engineering Journal, 2025)

Metalloporphyrin MOF-derived “quasi-carbon” materials featuring well-defined Co N4 sites as bifunctional electrocatalysts for enhanced zinc-air batteries performance - Yungang Sun; Kexin Xiong; Guoxin Zhang; Kairen Cheng; Shaoqing Feng; Huicong Chen; Meiyun Li; Kai Chen; Yihuang Chen; Huile Jin; Shun Wang (Chemical Engineering Journal, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Chemical constituents from the flowers of Inula japonica: Chemotaxonomic significance and antidiabetic activity - Jun-Li Cheng; Chang Yan; Hong-Fang Cai; Kai-Wen Kang; Dong-Li Li; Hong-Guang Li; Li-She Gan (Biochemical Systematics and Ecology, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

The Spatial Configuration and Force Analyses of Hoses in a Fully Hose-Based Conveyance System - Jun Li; Kai Zhan; Ming Zhang; Yangrui Cheng; Yingying Wang (Journal of Marine Science and Engineering, 2025)
The conveying hose is an important piece of equipment in the field of Marine engineering. Its spatial configuration and force conditions affect the normal operation of the Marine engineering system. This paper proposes a flexible, fully hose-based conveyance method for the field of deep-sea mining and mainly uses Orcaflex software to simulate and analyze the characteristics of the conveying hose in this system. This paper studies the influences of the top spacing, incoming flow direction, and placement and recovery processes on the configuration characteristics and force conditions of the hose. The conclusion drawn is that the conveying hose studied in this paper can maintain a good spatial configuration underwater and has a stable force condition. When the top spacing is 20 m, the transition of the curved section at the bottom of the hose is relatively smooth. The top tension of the hose has a good adaptability to the top spacing and the direction of the incoming flow. The conveying hose can stably complete the deployment and recovery operations.

Evolutionary Dynamics and Functional Conservation of amh Signaling in Teleost Lineages - Lingqun Zhang; Qingke Zhang; Kai Hu; Wei Lu; Weigang Li; Fengchi Wang; Jie Cheng (Fishes, 2025)
The anti-Müllerian hormone (amh) and its receptor, amhr2, along with the downstream bone morphogenetic protein receptors (bmprs), have been recognized as the central regulators in teleost sex determination (SD) and differentiation. However, their evolution and function in reproduction among diverse teleost lineages may represent species-specific patterns and still need more explanation. In this study, systematic investigations of amh signaling genes, including amh, amhy (Y-linked paralog of amh), amhr2, bmpr1, and bmpr2, were conducted among teleost species. The results revealed generally conserved gene copy number, phylogeny, structure, and synteny, among teleost amh signaling genes. Notably, significantly accelerated evolutionary rates (dN/dS) were found in teleost amhy compared to amh, and amh exhibited faster molecular evolution in amhy-SD teleosts than in non-amhy-SD teleosts, suggesting their enhanced evolutionary plasticity in teleosts. Expression profiling identified testis-biased expression of the most amh signaling genes in fish species with different SD genes and mechanisms, including Lateolabrax maculatus and Dicentrarchus labrax from Order Perciformes, Cynoglossus semilaevis and Paralichthys olivaceus from Order Pleuronectiformes, and Salmo salar and Oncorhynchus mykiss from Order Salmoniformes, with ovary-biased expression also found in Salmoniformes. A weighted gene co-expression network analysis further uncovered strong species-specific functional interactions between amh signaling components and genes of germ-cell development, the meiotic process, etc. Collectively, the integrated evidence from this study supports the hypothesis that amh signaling provides the key molecules governing sex differentiation in a species-specific manner in diverse teleost lineages, independent of its SD role, and interacts with functions of both testis and ovary development.

Fraxetin as a promising natural agent for controlling white spot syndrome virus: Mechanistic insights and application potential - Cheng Chen; Kai-Yuan Lu; Chang-Shuai Liang; Tao Liu; Qing Yu; Peng-Fei Li; Fei Ling; Gao-Xue Wang (Aquaculture, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Carboxymethyl-β-cyclodextrin grafted chitosan embedded oyster (Crassostrea gigas) ferritin can alleviate lead-induced liver injury by oral administration - Han Li; Shuzhen Cheng; Kai Zhou; Jiachen Zang; Zhenyu Wang; Ming Du (Food Research International, 2025)

A Chinese lantern-inspired low frequency energy harvester with synchronized multi-branched conversion elements - Tingting Chen; Kai Wang; Qiang Wang; Yiding Wang; Li Cheng; Jiaxi Zhou (Engineering Structures, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Research on all-day water vapour profile retrieval method based on lidar data and machine learning algorithm - Xiao Cheng; Huige Di; Qimeng Li; Ning Chen; Jiaying Yang; Kai Song; Dengxin Hua (International Journal of Remote Sensing, 2025)

Prophylactic effects of nirmatrelvir/ritonavir on reducing complications of cardiac surgery, reinfection, and post-acute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with previous SARS-CoV-2 infection: a randomized clinical trial (PEP Trial) - Xin Yuan; Lihua Zhang; Jingkuo Li; Lubi Lei; Kai Chen; Qing Chu; Wei Feng; Xiaoqi Wang; Zhaoyun Cheng; Yan Yang; Yang Wang; Hansong Sun; et al. (Science Bulletin, 2025)

Three-dimensional configuration optimization of X semi-dynamic rudder for fully appended AUV based on response surface methodology and NSGA-II - Kai Zhang; Liang Cheng; Qing Wang; Jiangxiong Li; Yinglin Ke (Ocean Engineering, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

Interannual succession of phytoplankton community in a canyon-shaped drinking water reservoir during the initial impoundment period: Taxonomic versus functional groups - Yi Hou; Ya Cheng; Kai Li; Meng Yang; Kangzhe Huang; Gang Ji; Ruikang Xue; Tinglin Huang; Gang Wen (Journal of Environmental Sciences, 2025)

Relationship between starch granule-associated proteins and in vitro digestibility of buckwheat starches: From the perspective of gelatinization degree - Jin Du; Zhen Lu; Kai Cheng; Changfeng Li; Hao Wu; Bin Xu; Jian-Ya Qian (Food Chemistry, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Polygonatum cyrtonema Hua polysaccharide alleviates ulcerative colitis via gut microbiota-independent modulation of inflammatory immune response - Jin-Yang Shi; Yong-Jian Wang; Qian-Wen Bao; Ya-Min Qin; Pei-Pei Li; Qiao-Qiao Wu; Cheng-Kai Xia; De-Ling Wu; Song-Zi Xie (Carbohydrate Polymers, 2025)

Next Generation Air Quality Models: Dynamical Mesh, New Insights into Mechanism, Datasets and Applications - Jinxi Li; Yijie Li; Zifa Wang; Jiang Zhu; Lei Kong; Jie Li; Huangjian Wu; Leisheng Li; Xiao Tang; Zhen Cheng; Lanyi Zhang; Pu Gan; et al. (Current Pollution Reports, 2025)
Purpose of Review Air quality modelling and forecasting have been well recognised to play important roles in environmental research as well as government policy assessments and management strategies. To address the recent progresses in air quality modelling, we conduct a literature review focusing on air quality forecasting models and reanalysis datasets. Recent Findings First of all, the implementation of three-dimensional adaptive meshes/horizontal resolution-variable grids in air quality models offers a crucial insight on multi-scale simulations down to the hectometre level. These models balance high accuracy with computational efficiency. Secondly, current reanalysis still has limitations in its horizontal resolution (dozens of kilometres) that are insufficient to support the analysis and management of air pollution at factory levels or neighbourhood scales. The development of adaptive mesh resolution method provides a promising way to deal with this issue and allows the construction of the chemistry reanalysis at ultra-high resolutions (< 1 km). However, the use of adaptive mesh method in data assimilation is currently still restricted to the column-based one-dimensional models. Thirdly, the application of graphics processing units to air quality predictions enables more optimised resource usage and enhances model performance through hardware acceleration effects, while machine learning methods can both maintain the consistency with numerical solutions and increase the accuracy of air quality predictions for specific chemical species. Furthermore, parameters that describe more complicated processes and mechanisms have been added into pre-existing physical and chemical parameterisations to enable more accurate representation of various small-scale features, such as the parameterisation of inorganic chemistry on the surface of aerosols, as well as various photolysis schemes. Summary The increase of resolution brings computational burdens and shifts the boundary of resolved and sub-grid phenomena in air quality prediction, which in turn stimulates the development and usage of new technologies (e.g. adaptive mesh techniques, graphics processing unit acceleration, machine learning methods). They are conducive to the improvement of prediction accuracies and the acquisition of new insights on atmospheric physical and chemical mechanisms. However, new challenges also ensued, including the selection criteria for mesh refinement, the acquisition of high-resolution observational data and the integration of artificial intelligence-hybrid air quality models. More efforts are required to develop the adaptive irregular mesh grid data assimilation method to overcome the resolution problems of current chemical reanalysis.

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

The NiO hole transport layer between BiVO4 and Ni5P4 for photoelectrochemical water oxidation to hydrogen peroxide - Kai Cheng; Junyu Ren; Jingkun Wang; Naik Muhammad; Yupeng Chen; Fangzhou Zhou; Junjie Guo; Dong Duan; Tianbao Li; Bingshe Xu (Chemical Engineering Journal, 2025)

Etiological characterization of multiple recombinant lineages of TJ-C6 porcine reproductive and respiratory syndrome virus in Tianjin, Northern China - Yong Li; Cheng Yang; Xin-lei Li; Jiu-ying Sun; Ning Cheng; Kai-yue Wang; Ying-Feng Sun (Veterinary Research Communications, 2025)

Revealing ionically isolated Li loss in practical rechargeable Li metal pouch cells - Xiangrui Duan; Yuanjian Li; Kai Huang; Shuibin Tu; Guocheng Li; Wenyu Wang; Hongyu Luo; Zihe Chen; Chunhao Li; Kai Cheng; Xin-Xin Wang; Li Wang; et al. (Science Bulletin, 2025)

Stress-responsive plasma membrane H+-ATPases regulate deep rooting in rice - Di Wang; Kai Xu; Shoujun Chen; Lei Wang; Qiaojun Lou; Changsen Zhong; Yawen Wang; Tiemei Li; Huaxiang Cheng; Lijun Luo; Liang Chen (Plant Science, 2025)

Revealing atomistic mechanism of lithium diffusion in montmorillonite structure: A molecular simulation study - Qin Li; Xiandong Liu; Kai Wang; Yongxian Cheng; Zhe Yin; Rucheng Wang; Xiancai Lu (Geochimica et Cosmochimica Acta, 2025)

Transcriptomics-based revelation of the effect of daidzein on the possible synthesis pathway of selenium-enriched exopolysaccharides in Monascus purpureus - Hong Li; Linchun Wang; Gang Wang; Kai Cheng; Wentao Pan; Meijian Hu; Jianhua Xie; Zhibing Huang (Food Bioscience, 2025)

Enhancing the preservation of blueberry with a tough and biodegradable soy protein isolate-carboxymethyl chitosan film integrated with TiO2 nanotube arrays - Kai Cheng; Fengfeng Xu; Jin Du; Changfeng Li; Zengkai Wang; Liwei Zhang; Xueqin Wang; Jun Liu (Food Packaging and Shelf Life, 2025)

Revealed mechanism of 3D-open-microarray boosting exoelectrogens Geobacter enrichment and extracellular electron transfer for high power generation in microbial fuel cells - Da Liu; Chao-qun Xu; Wen-kai Fang; Cheng-yu Li (Bioresource Technology, 2025)

Large-deformation analyses of seismic landslide runout considering spatially random soils and stochastic ground motions - Shun-Ping Ren; Yang Li; Xue-Jian Chen; Po Cheng; Fei Liu; Kai Yao (Bulletin of Engineering Geology and the Environment, 2025)

Identification of the arachidonic acid 5-lipoxygenase and its function in the immunity of Apostichopus japonicus - Jiahao Cheng; Kai Yang; Xu Li; Benkang Liu; Ming Chen; Cheng Li (Fish & Shellfish Immunology, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Microfluidic investigation on microscopic flow and displacement behavior of CO2 multiphase system for CCUS-EOR in heterogeneous porous media - Cheng Qian; Zhenhua Rui; Yueliang Liu; Kaihu Zhou; Kai Du; Yang Zhao; Jirui Zou; Kaoping Song; Xintong Li (Chemical Engineering Journal, 2025)

Assessment of pollution sources and health risks of black carbon aerosols in industrial cities of Northwestern China using light absorption observations - Kai Cheng; Yuting Zhong; Xia Li; Shuting Li; Maulen Ayitken; Wang Zhang; Xinchun Liu (Atmospheric Pollution Research, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Biological Traits of Spodoptera litura (Fabricius) in Response to Joint Application of Beauveria bassiana (Balsamo)Vuillemin and Emamectin Benzoate - Jiaying Li; Qingsong Cheng; Lin Chen; Kai Teng; Weiai Zeng; Hailin Cai; Shen Zhang; Zhipeng Xiao; Shaolong Wu; Bin Hu; Zhenxing Zhao; Hongwu Yang; et al. (Journal of Crop Health, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Performance assessment of multiple ambiguity resolution methods in single LEO precision orbit determination - Mengmeng Li; Xingyu Zhou; Qianxin Wang; Kai Li; Ming Gao; Tong Cheng; Han Zhang (Advances in Space Research, 2025)

Molecular Cloning and Functional Analysis of Secretory Phospholipase A2 from Apostichopus japonicus - Cheng Li; Lili Yang; Zhongyun Zhang; Ying Liu; Xu Li; Kai Yang; Ming Chen (Biochemical Genetics, 2025)

α-Linolenic acid promotes testosterone synthesis by improving mitochondrial function in primary rooster Leydig cells - Xuerui Chang; Danyang Li; Yong Guo; Xihui Sheng; Xiangguo Wang; Kai Xing; Longfei Xiao; Xueze Lv; Cheng Long; Xiaolong Qi (Theriogenology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

New quantified climate reconstruction in southern China suggests a potential influence of winter cloud cover across East Asia during the Holocene - Xiao Zhang; Cong Chen; Kexin Wang; Meihuan Li; Yuanfu Yue; Jun Cheng; Mengna Liao; Kai Li; Lina Liu; Zhanghua Wang; Rachid Cheddadi; Qiuchi Wan; et al. (Science of The Total Environment, 2025)

Genetic estimation of fat traits in sheep and association of its NR1H4 gene polymorphisms with tail fat deposition - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yuan zhao; Yukun Zhang; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Characteristics and potential human health risks of Paralytic Shellfish Toxins identified in eight species of bivalves from South Yellow Sea Mudflat - Cheng Ding; Jinling Wu; Qingyuan Guo; Jiaxuan Luan; Kai Yang; Zhaoxia Li; Xuan Li; Jianwei Yu; Feng Liang; Bairen Yang; Tianming Chen (Aquatic Toxicology, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Polystyrene microplastics alleviate the developmental toxicity of silver nanoparticles in embryo-larval zebrafish (Danio rerio) at the transcriptomic level - Qiao-hong Xiao; Hao Xiang; Ya-nan Tian; Jiao-long Huang; Ming-qun Li; Pu-qing Wang; Kai Lian; Peng-xia Yu; Meng-yao Xu; Ruo-nan Zhang; Yan Zhang; Jie Huang; et al. (Science of The Total Environment, 2024)

Remote sensing of air pollutants in China to study the effects of emission reduction policies on air quality - Gerrit de Leeuw; Ronald van der A; Jianhui Bai; Mirjam den Hoed; Jieying Ding; Jianping Guo; Zhengqiang Li; Ying Zhang; Cheng Fan; Kai Qin; Selviga Sinnathamby; Sarah Safieddine; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Structural characterization of oligosaccharide from Dendrobium officinale and its properties in vitro digestion and fecal fermentation - Hao Cheng; Lei Xu; Hua Zhu; Tingting Bu; Zhenhao Li; Shuna Zhao; Kai Yang; Peilong Sun; Ming Cai (Food Chemistry, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Demonstration of the carbon capture with building make-up air unit - Poorandokht Ilani-Kashkouli; Jamieson Brechtl; Keju An; Michelle Kidder; Costas Tsouris; Christopher Janke; Stephen Kowalski; Cheng-Min Yang; M. Muneeshwaran; Meghan Lamm; Katie Copenhaver; Brian Fricke; et al. (Energy and Buildings, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Polyelectrolyte intercalated two-dimensional covalent organic framework membranes for efficient desalination - Beixi Jia; Yu Zheng; Zhichao Li; Kai Xu; Hui Wang; Lijuan Cheng; Hongjian Wang; Zhuang Liu; Runnan Zhang; Zhongyi Jiang (Desalination, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

Abundance, characteristics and ecological risks of microplastics from South Yellow Sea Mudflat - Qingyuan Guo; Cheng Ding; Qingqin Meng; Xiaomei Shen; Kai Yang; Zhaoxia Li; Xiao Chen; Chunmiao Wang; Jinling Wu; Jianwei Yu; Xuan Li; Feng Liang (Science of The Total Environment, 2024)

Dynamic mechanical properties and microstructure of ultrafine slag powder cement paste utilizing solid waste industrial tailings powder and fly ash - Hang Zou; Shitang Cui; Kai Zhao; Jingsong Cheng; Zhijun Zheng; Shengjun Li; Yongliang Zhang (Process Safety and Environmental Protection, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Response of the algal-bacterial community to thermal stratification succession in a deep-water reservoir: Community structure, co-assembly patterns, and functional groups - He Lv; Meng Yang; Ya Cheng; Kai Li; Tinglin Huang; Gang Wen (Environmental Research, 2024)

Synergistic implementation of efficient adsorption-diffusion-conversion in lithium-sulfur batteries via built-in electric field constructed by transition metal selenides - Jun Wang; Kai Huang; Qi Li; Guo Cheng; Yongzheng Zhang; Na Teng; Cheng Lian; Cheng Ma; Jitong Wang; Wenming Qiao; Licheng Ling (Chemical Engineering Journal, 2024)

Pagoda solar evaporators with an alternating hot-cold pattern for rapid, scaling-free desalination of hypersaline brines - Zhenwei Wu; Kai Li; Ran Deng; Yu-Ren Xue; Hao-Nan Li; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2024)

Study on the effects of electrode volume fraction and electrode particle radius on dynamic electrochemical-thermal-aging coupling characteristics of lithium cell based on cylindrical cell design method - Xu-Dong Yuan; Zhen-Kai Xiong; Lian-Cheng Li; Chuan-Ye Tang; Qi-Wei Jia; Hong-Chuan Tuo; Yan Zhang (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Disentangling the assembly patterns and drivers of microbial communities during thermal stratification and mixed periods in a deep-water reservoir - He Lv; Meng Yang; Ya Cheng; Kai Li; Gang Ji; Tinglin Huang; Gang Wen (Science of The Total Environment, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Expression of ovine MYH3 gene and its polymorphisms and association analysis with growth traits in Hu sheep - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yukun Zhang; Yuan Zhao; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2024)

Rock-physics modeling and pre-stack seismic inversion for the Cambrian superdeep dolomite reservoirs in Tarim Basin, Northwest China - Shi-Kai Jian; Li-Yun Fu; Wensheng Duan; Gengxin Peng; Suo Cheng; Yongliang Tang; Duoming Zheng (Marine and Petroleum Geology, 2024)

Numerical study of the future PM2.5 concentration under climate change and best-health-effect (BHE) scenario - Dongqing Li; Qizhong Wu; Huaqiong Cheng; Jinming Feng; Dongxing Li; Yongli Wang; Kai Cao; Lanning Wang (Environmental Pollution, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Investigation on the interaction of NH3&CH4 co-activated char under reburning conditions - Yukai Li; Shaozeng Sun; Dongdong Feng; Kai Geng; Zhenyu Cheng; Wenda Zhang; Yijun Zhao; Wenming Yang (Journal of Environmental Management, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Hybrid cell membranes camouflaged copper-loaded nano-prodrug for tumor angiogenesis inhibition and cell cuproptosis - Xian Qin; Li Zhu; Xuan An; Cheng Zhang; Jiawei Li; Fei Yan; Wenjin Zhang; Kai Qu; Kun Zhang; Wei Wu; Guicheng Wu (Chemical Engineering Journal, 2024)

Aβ1−42 stimulates an increase in autophagic activity through tunicamycin-induced endoplasmic reticulum stress in HTR-8/SVneo cells and late-onset pre-eclampsia - Qian Gao; Kai Cheng; Leiming Cai; Yuping Duan; Yan Liu; Zhiwen Nie; Qian Li (Journal of Molecular Histology, 2024)

Effect of exogenous acylhomoserine lactone 3-oxo-C14-HSL on the performance of biofilm in moving bed biofilm reactor - Zhifei Li; Junlin Li; Wangbao Gong; Kai Zhang; Guangjun Wang; Yun Xia; Mengyuan Yu; Wenping Xie; Zhuoyin Lu; Xiangju Cheng; Jun Xie (Journal of Water Process Engineering, 2024)

Effect of Ce2O3 phase transition on the catalytic oxidation for toluene over CeO2 catalysts - Guanqing Cheng; Zhongxian Song; Yanli Mao; Jingfei Zhang; Kai Wang; Haiyang Li; Zhenzhen Huang (Fuel, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

The alpha2-adrenergic receptor agonist clonidine protects against cerebral ischemia/reperfusion induced neuronal apoptosis in rats - Zhi He; Bo-Kai Yin; Ke Wang; Bo Zhao; Yue Chen; Zi-Cheng Li; Jing Chen (Metabolic Brain Disease, 2024)

Comparative analysis of the growth performance, vitality, body chemical composition and economic efficiency of the main cultivated strains of Pacific white shrimp (Litopenaeus vannamei) in coastal areas of China - Cheng Zhang; Chun-Yang Guo; Kai-He Shu; Shan-Liang Xu; Dan-Li Wang (Aquaculture, 2024)

Effects of cultural landscape service features in national forest parks on visitors’ sentiments: A nationwide social media-based analysis in China - Yingyi Cheng; Bing Zhao; Siqi Peng; Kai Li; Yue Yin; Jinguang Zhang (Ecosystem Services, 2024)

Systems metabolic engineering of Corynebacterium glutamicum to assimilate formic acid for biomass accumulation and succinic acid production - Kai Li; Xue Zhang; Cheng Li; Yu-Cheng Liang; Xin-Qing Zhao; Chen-Guang Liu; Anthony J. Sinskey; Feng-Wu Bai (Bioresource Technology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Hydrogen-bond tuned conjugated architectures for nitric oxide sensing in single-benzene framework: Advances and mechanistic insights - Feng-Zao Chen; Cun-Bin Du; Yi-Chao Wang; Jie Zhu; Ge Cheng; Kai-Bin Li; De-Man Han; Xiao-Yu Wu (Analytica Chimica Acta, 2024)

Asiaticasics A-O, structurally intriguing coumarins from Toddalia asiatica with potential inflammatory inhibitory activity - Si-Chen Song; Bai-Dong Ren; Xue-Wen Wu; Yi-Fan Xie; Bin Cheng; Qiong Wei; Wen-Hui Pang; Ze-Kai Wu; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2024)

Core-shell DOPO/caramel nano-polymer with desirable UV shielding and flame retardancy for polyamide 6 fabric - Wen-Jie Jin; Xian-Wei Cheng; Sheng-Nan Ma; Ling Li; Rui-Kai Wu; Jin-Ping Guan (Chemical Engineering Journal, 2024)

Development of similar materials with different tension-compression ratios and evaluation of TBM excavation - Jing Wang; Yaming Zhang; Kai Wang; Liping Li; Shuai Cheng; Shangqu Sun (Bulletin of Engineering Geology and the Environment, 2024)

Geochemical and U-Pb isotopic insights into uranium (U) enrichment in the soil around a nuclear fuel element plant, in Southwest China - Xin Cheng; Jianing Sun; Kai Ling; Keyi Zhong; Bolin Shao; Lan Li; Shanshan Zhao; Yi Huang; Hao Song; Bo Cheng (Ore and Energy Resource Geology, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Effects of chemical mechanism and meteorological factors on the concentration of atmospheric pollutants in the megacity Beijing, China - Yujie Li; Qizhong Wu; Xiaoyan Wang; Huaqiong Cheng; Yiming Sun; Dongqing Li; Kai Cao; Xueying Wang; Shurui Yang (Atmospheric Environment, 2024)

Source apportionment and health risk assessment of PM2.5-bound elements on winter pollution days in industrial cities on the northern slope of Tianshan Mountain, China - Kai Cheng; Youjiang He; Yuting Zhong; Xia Li; Shuting Li; Maulen Ayitken (Atmospheric Pollution Research, 2024)

Asymmetric disturbance and permeabilization of bilayer membranes by 3-nm carbon dots - Wenwen Li; Yurong Ma; Luping Ou; Cheng Xu; Yushuang Wei; Kai Yang; Bing Yuan (Journal of Hazardous Materials, 2024)

Ozone exposure affects corneal epithelial fate by promoting mtDNA leakage and cGAS/STING activation - Kai Fan; Nuo Dong; Meichai Fang; Zixun Xiang; Lan Zheng; Mengyuan Wang; Yukuan Shi; Gang Tan; Cheng Li; Yuhua Xue (Journal of Hazardous Materials, 2024)

Boosting the CO2 electrolysis performance using high entropy stable La0.2Pr0.2Sm0.2Sr0.2Ca0.2Fe0.9Ni0.1O3-δ electrode for symmetric solid oxide electrolysis cells - Zhengpeng Chen; Jiajia Wang; Mingfei Li; Jiangbo Dong; Renci Xu; Jinsong Cheng; Kai Xiong; Mumin Rao; Chuangting Chen; Chenjin Shen; Xiaowei Li; Yihan Ling (Fuel, 2024)

Lightweight, flame retardant Janus carboxymethyl cellulose aerogel with fire-warning properties for smart sensor - Yide Liu; Fangfang Cheng; Kai Li; Jiuyong Yao; Xiankai Li; Yanzhi Xia (Carbohydrate Polymers, 2024)

Instantaneous inversion of transient electromagnetic data using machine learning - Kai Cheng; Maoxin Su; Yiguo Xue; Daohong Qiu; Guangkun Li (Acta Geophysica, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

Harsh environment resistible and recyclable thermoplastic polyurea adhesive based on stable and density hydrogen bonds - Dongqi Wang; Kai Yang; Sisi Cheng; Meishan Fu; Zhihong Wang; Lixia Li; Xin Zhao; Lijing Han; Wenzhi Ren; Fang Yang; Ruoyu Zhang (Chemical Engineering Journal, 2024)

Adequate nutrient intake mitigate the toxic effects of bromate on the rotifer Brachionus calyciflorus - Tao Chen; Xiao-Ping Xu; Jin-Cheng Li; Kai-Yan Tao; Chang-Shuang Zhao (Environmental Science and Pollution Research, 2024)

Interannual variation and machine learning simulation of organophosphate esters in Taihu Lake - Yuteng Zhang; Xinying Cheng; Xianxian Chen; Lei Ding; Hui Xiao; Kai Liu; Shaogui Yang; Huiming Li; Huan He (Journal of Hazardous Materials, 2024)

Cross-scale coupling analysis method for OTSG in SFR and its application - Zhenguo Zhang; Xiaochang Li; Sichao Tan; Ruifeng Tian; Kai Liu; Hui Cheng (Annals of Nuclear Energy, 2024)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Mechanism of low-voltage electrostatic fields on the water-holding capacity in frozen beef steak: Insights from myofilament lattice arrays - Yong Xie; Kai Zhou; Bo Chen; Yunhao Ma; Cheng Tang; Peijun Li; Zhaoming Wang; Feiran Xu; Cong Li; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Removal of Colorants from Sugarcane Juice and Remelt Syrup by Bagasse-Based Biochar–Hydroxyapatite Composites - Cheng Wang; Wende Lu; Mengying Luo; Caifeng Xie; Kai Li; Fangxue Hang (Sugar Tech, 2023)

Production of all-male non-transgenic zebrafish by conditional primordial germ cell ablation - Fang Wang; Yong-Yong Feng; Xu-Guang Wang; Mi Ou; Xin-Cheng Zhang; Jian Zhao; Kun-Ci Chen; Kai-Bin Li (Fish Physiology and Biochemistry, 2023)

Endophytic Bacillus sp. R1 and Its Roles in Assisting Phytoremediation and Alleviating the Toxicity of Aluminum Combined Phenanthrene Contaminations in Brassica napus - Li-rong Fang; Xue-cheng Yang; Chun-ya Wu; Kai Sun; Mallavarapu Megharaj; Wei He (Current Microbiology, 2023)

Potential and Characteristics of Methane Production During Anaerobic Digestion of Cabbage Waste at Different Temperatures - Cheng Liao; Kaijing Li; Changmei Wang; Chengyue Liang; Xingling Zhao; Kai Wu; Bin Yang; Fang Yin; Wudi Zhang (BioEnergy Research, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Tailor-made yolk-shell nanocomposites of star-shape Au and porous organic polymer for nitrogen electroreduction to ammonia - Hongming He; Hao-Ming Wen; Ping Li; Hong-Kai Li; Cheng-Peng Li; Zhihong Zhang; Miao Du (Chemical Engineering Journal, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

A Novel Large-Scale Three-Dimensional Physical Model Experimental System for Deep Underground Engineering - Xia-Ting Feng; Zheng-Wei Li; Shi-Ming Mei; Jun Tian; Cheng-Xiang Yang; Zhi-Bin Yao; Ji-Kai Gao (Rock Mechanics and Rock Engineering, 2023)

Clinical characteristics and prognostic risk factors of candidemia in non-neutropenic patients: a retrospective cohort study - Fengqi Liu; Xueping Shao; Zhaohui Dong; Kankai Tang; Li Zhong; Wei Xu; Zhidong Chen; Cheng Zheng; Kai Zhang; Jiachang Cai; Hongwei Zhou; Wei Cui; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Association of urinary heavy metal combined exposure with periodontitis among US adults from NHANES 2011–2014 - Zhen-Hua Li; Jiong Li; Yi-Cheng Mao; Jia-Wen Zhao; Hui-Yu Hu; Sun Zhang; Zhe-Ye Liu; Xue-Jie Liu; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Science and Pollution Research, 2023)

Open-framework hybrid zinc/tin selenide as an ultrafast adsorbent for Cs+, Ba2+, Co2+, and Ni2+ - Yang Liu; Feng-Qi Shi; Xin Hao; Meng-Yu Li; Lin Cheng; Cheng Wang; Kai-Yao Wang (Journal of Hazardous Materials, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Mechanism behind the deterioration in gel properties of collagen gel induced by high-temperature treatments: A molecular perspective - Cheng Tang; Yujuan Xu; Kai Zhou; Yong Xie; Yunhao Ma; Cong Li; Feiran Xu; Hui Zhou; Baocai Xu (Food Research International, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effect of gaseous pollutant and greenness exposure on mortality during treatment of newly treated tuberculosis patients: a provincial population-based cohort study - Jia-Wen Zhao; Xin-Qiang Wang; Zhen-Hua Li; Yi-Cheng Mao; Sun Zhang; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang; Xiao-Hong Kan (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Mechanism of textural properties changes of cooked chicken in early postmortem: Effect of protein degradation induced by calpain on heating shrinkage - Yunhao Ma; Ying Wang; Zhaoming Wang; Bo Chen; Yong Xie; Cheng Tang; Cong Li; Kai Zhou; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Thermo-lp: A computational tool to evaluate reaction thermodynamics for synthesizing M+1AX (MAX) phases based on linear programming optimization method - Xianghui Feng; Nan Li; Kai Wu; Yonghong Cheng; Bing Xiao (Computer Physics Communications, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Comparative analysis of the gut microbiota of wild wintering whooper swans (Cygnus Cygnus), captive black swans (Cygnus Atratus), and mute swans (Cygnus Olor) in Sanmenxia Swan National Wetland Park of China - Jun-Xian Mi; Kai-Li Liu; Wen-Li Ding; Ming-Hui Zhang; Xue-Fei Wang; Aftab Shaukat; Mujeeb Ur Rehman; Xi-Lan Jiao; Shu-Cheng Huang (Environmental Science and Pollution Research, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Low ambient temperature increases the risk and burden of atrial fibrillation episodes: A nationwide case-crossover study in 322 Chinese cities - Xinlei Zhu; Renjie Chen; Yong Zhang; Jialu Hu; Yixuan Jiang; Kai Huang; Jianan Wang; Wei Li; Bei Shi; Yundai Chen; Lang Li; Bao Li; et al. (Science of The Total Environment, 2023)

Selective flotation separation of hemimorphite from quartz using the biosurfactant sodium N-lauroylsarcosinate as a novel collector - Kai Jia; Yuhang Lu; Jiang Liu; Shun Cheng; Shiqiang Liu; Yijun Cao; Guosheng Li (Minerals Engineering, 2023)

Water-lifting and aeration system improves water quality of drinking water reservoirs: Biological mechanism and field application - Liqing Kou; Tinglin Huang; Haihan Zhang; Kai Li; Fengyao Hua; Cheng Huang; Xiang Liu; Fan Si (Journal of Environmental Sciences, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Large-scale assessment of exposure to legacy and emerging per- and polyfluoroalkyl substances in China's shorebirds - Jiachen Sun; Yachang Cheng; Zitan Song; Shisheng Ma; Lingling Xing; Kai Wang; Chenjing Huang; Donglai Li; Jiansong Chu; Yang Liu (Environmental Research, 2023)

Hexavalent chromium disrupts the skin barrier by targeting ROS-mediated mitochondrial pathway apoptosis in keratinocytes - Cheng Wang; Hongqi Shang; Shuyu Zhang; Xiangkun Wang; Defeng Liu; Mingyue Shen; Ning Li; Yunxuan Jiang; Kai Wei; Ruiliang Zhu (Chemico-Biological Interactions, 2023)

Characteristics of antibiotic resistance genes and microbial community distribution in Wanfeng Lake, upper Pearl River, China - Yuntao Zhang; Jiang Li; Tianyu Wu; Kai Ma; Zhentao Cheng; Qianwen Yi; Yongheng Dai; Bin Wang; Yu Chen; Bin Wang; Xia Hu; Aijiang Yang; et al. (Environmental Science and Pollution Research, 2023)

Emodin alleviates testicular ischemia-reperfusion injury through the inhibition of NLRP3-mediated pyroptosis - Kai-Xiang He; Jin-Zhuo Ning; Wei Li; Fan Cheng (Tissue and Cell, 2023)

Field trial assessing the antimicrobial decontamination efficacy of gaseous ozone in a public bus setting - Erica Sena Neves; Cheng Teng Ng; Han Bin Pek; Vanessa Shi Li Goh; Roslinda Mohamed; Sheereen Osman; Yi Kai Ng; Sharain Abdul Kadir; Mohammad Nazeem; Alan She; Glenndle Sim; Joel Aik; et al. (Science of The Total Environment, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Extraction of scattered and precious metals from lead anode slime: A short review - Zhe Gao; Xiangfeng Kong; Bin Yang; Jiafei Yi; Kai Fan; Tongyu San; Keke Cheng; Shaoxiong Li; Dachun Liu; Baoqiang Xu; Wenlong Jiang (Hydrometallurgy, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Functionalization of inert silica to construct Si-O-Ni interfacial sites for stable dry reforming of methane - Kai Feng; Shuairen Qian; Zhihe Zhang; Zhengwen Li; Xiaohang Sun; Yi Cheng; Binhang Yan (Chemical Engineering Journal, 2023)

Engineering Corynebacterium glutamicum for efficient production of succinic acid from corn stover pretreated by concentrated-alkali under steam-assistant conditions - Kai Li; Cheng Li; Xin-Qing Zhao; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2023)

Identification and evaluation of fishy odorants produced by four algae separated from drinking water source during low temperature period: Insight into odor characteristics and odor contribution of fishy odor-producing algae - Qingyuan Guo; Xiao Chen; Kai Yang; Jianwei Yu; Feng Liang; Chunmiao Wang; Bairen Yang; Tianming Chen; Zhaoxia Li; Xuan Li; Cheng Ding (Chemosphere, 2023)

Pathogenicity of duck circovirus and fowl adenovirus serotype 4 co-infection in Cherry Valley ducks - Mingyue Shen; Panpan Gao; Cheng Wang; Ning Li; Shuyu Zhang; Yunxuan Jiang; Defeng Liu; Baoyu Jia; Li Xu; Bohan Huang; Ruiliang Zhu; Kai Wei (Veterinary Microbiology, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Local singularity and S–A methods for analyzing ore-producing anomalies in the Jianbiannongchang area of Heilongjiang, China - Zhonghai Zhao; Kai Qiao; Yiwen Liu; Xiaomeng Cui; Binbin Cheng; Shanshan Liang; Chenglu Li (Acta Geochimica, 2023)

Effects of ammonia on morphological characteristics and nanostructure of soot in the combustion of diesel surrogate fuels - Kai Zhang; Yishu Xu; Yu Li; Yang Liu; Bowen Wang; Huakun Wang; Jingjing Ma; Xiaobei Cheng (Journal of Hazardous Materials, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Fe, N, S co-doped cellulose paper carbon fibers as an air-cathode catalyst for microbial fuel cells - Demin Jiang; Huina Chen; Hao Xie; Kai Cheng; Liang Li; Kun Xie; Yuqiao Wang (Environmental Research, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

The influence of anthropogenic emissions on air quality in Beijing-Tianjin-Hebei of China around 2050 under the future climate scenario - Dongqing Li; Qizhong Wu; Jinming Feng; Yongli Wang; Lanning Wang; Qi Xu; Yiming Sun; Kai Cao; Huaqiong Cheng (Journal of Cleaner Production, 2023)

Chemical constituents from Lagopsis supina and their chemotaxonomic significance - Kai Wang; Stanislas Nsanzamahoro; Pei-Lin Li; Tian Chai; Cheng-Bo Wang; Chun-Yan Sang; Jun Wang; Jun-Li Yang (Biochemical Systematics and Ecology, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Residue depletion of danofloxacin in Yellow River carp (Cyprinus carpio haematopterus) following multiple oral administration - Zhe-Wen Song; Fang Yang; Yue Liu; Hao-Tian Shao; Mei Zhang; Jun-Cheng Chen; Kai-Li Ma; Fan Yang (Aquaculture, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Catalytic pyrolysis of spent bleaching clay for its regeneration and simultaneously producing aromatic hydrocarbons - Kai Li; Zhu-yu Li; Cheng-Bo Zhang; Jia-qi Zhao; Li Zhao; Ji Liu; Shan-wei Ma; Qiang Lu (Journal of Cleaner Production, 2023)

Covalent organic framework@Ti3C2T composite as solid phase microextraction coating for the determination of polycyclic aromatic hydrocarbons in honey samples - Yuanqing Zhao; Kai Hu; Cheng Yang; Xiaobing Liu; Lixin Li; Zhonghua Li; Pan Wang; Zhenqiang Zhang; Shusheng Zhang (Analytica Chimica Acta, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Passive Cavitation Enhancement Mapping via an Ultrasound Dual-Mode phased array to monitor blood-brain barrier opening - Trung Nguyen Hoang; Hsiang-Ching Lin; Chih-Hong Tsai; Cheng-Kai Jan; Hao-Li Liu (Journal of Medical and Biological Engineering, 2022)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Chemical constituents from the aerial part of Polygala tenuifolia - Yan-Gang Cheng; Jin-Yan Tan; Jian-Li Li; Shi-Hui Wang; Kai-Li Liu; Jia-Min Wang; Ying-Li Wang (Natural Product Research, 2022)

Preparation of Hypercrosslinked Polymer-Based Sponge and its Application for the Removal of Non-Steroidal Anti-Inflammatory Drugs in Water Samples - Pengzhao Han; Kai Hu; Lixin Li; Yuanqing Zhao; Cheng Yang; Xiaobing Liu; Shusheng Zhang; Yanjie Huang (Water, Air, & Soil Pollution, 2022)

Salinimicrobium sediminilitoris sp. nov., Isolated from a Tidal Flat - Cheng-Qiang Xia; Hui-Jing Niu; Kai-Shi Dong; Li Guan; Li-Ping Sun; Qin Wang; Yan-Jiao Zhang; Yi Li; Cai-Xia Pei (Current Microbiology, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Boron isotope geochemistry of Bangor Co Salt Lake (central Tibet): implications for boron origin and uneven mixing of lake water - Bin-Kai Li; Mao-Yong He; Hai-Zhou Ma; Huai-De Cheng; Lian-Min Ji (Acta Geochimica, 2022)

In-situ radon-in-water detection for high resolution submarine groundwater discharge assessment - Shibin Zhao; Meng Li; William C. Burnett; Kai Cheng; Chunqian Li; Jinjia Guo; Songling Yu; Wen Liu; Tong Yang; Natasha T. Dimova; Guangquan Chen; Zhigang Yu; et al. (Frontiers in Marine Science, 2022)
Submarine groundwater discharge (SGD), including both land-based fresh groundwater that enters the ocean from coastal aquifers as well as recirculated seawater that is continuously recharged and discharged on the seabed, has been considered as an important component of the global water and biogenic element (e.g., nitrogen, phosphorus, silicon and carbon) sources and a significant pathway for material exchange at the land-sea interface of coastal ecosystems. Some researchers reported that SGD associated nutrient additions to coastal waters have caused unwanted ecological issues, including red tides, coastal acidification and hypoxia. Natural radon isotope ( 222 Rn, t 1/2 = 3.8 d ) is an excellent tracer for studying SGD and other oceanographic processes including air-sea gas exchange, sediment-water diffusion, and earthquake prediction. However, the conventional radon measurement methods suffer many technical disadvantages. We consequently developed a convenient submersible radon determination approach (“OUC-Rn”) using a commercial pulsed ionization chamber (PIC) radon sensor and gas extraction membrane module to produce high precision and high resolution observations. We demonstrate the radon degassing efficiency of the membrane contactor is comparable to the shower-head type air-water exchanger but is independent of operating position. The radon measurement efficiency of the PIC is 2-fold higher than the RAD7 detector and is far less influenced by moisture. We successfully deployed the system in 2.5 meters water depth over a 100 hours period in an anthropogenic influenced bay. Based on our high temporal resolution observations, the SGD flux was estimated to be 0-43.0 cm/d (mean: 25.4 ± 14.5 cm/d). The SGD fluxes pattern plotted together with the tidal variations revealed that tidal pumping may be the main force driving seawater recirculation into aquifers and thus affecting nutrient, carbon and other dissolved matters dynamics in coastal regions.

Feasibility of Artificial Materials in Simulating Rock Failure Based on Rate-Dependent Brittleness Indexes - Chunjiang Zou; Suo Yingying; Kai Liu; Yi Cheng; Jianchun Li (Rock Mechanics and Rock Engineering, 2022)

The coordinated alterations in antioxidative enzymes, PeCu/ZnSOD and PeAPX2 expression facilitated in vitro Populus euphratica resistance to salinity stress - Kai Feng; Jinling Lu; Ying Chen; Yongya Luo; Yuchen Hu; Xuexia Li; Songzheng Zhong; Le Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Short-term effect of sulfur dioxide (SO2) change on the risk of tuberculosis outpatient visits in 16 cities of Anhui Province, China: the first multi-city study to explore differences in occupational patients - Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Ying-Qing Li; Xin Cheng; Zhen-Hua Li; Yi-Cheng Mao; Cheng-Yang Hu; Kai Huang; Kun Ding; et al. (Environmental Science and Pollution Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Comprehensive investigation of water-conducting channels in near-sea limestone mines using microtremor survey, electrical resistivity tomography, and tracer tests: a case study in Beihai City, China - Maoxin Su; Kai Cheng; Haiyan Li; Yiguo Xue; Peng Wang; Xiaoyin Ma; Congcong Li (Bulletin of Engineering Geology and the Environment, 2022)

Quantitative detection of parasitic ciliate Cryptocaryon irritans in seawater with an optimized sample processing method - Jia‐Jia Tang; Zhi‐Hong Zhong; Zhi‐Cheng Li; Qing‐Kai Guo; Shi‐Yu Li; Yi‐Xuan Guo; Biao Jiang; An‐Xing Li (Journal of Fish Diseases, 2022)
The protozoan Cryptocaryon irritans is one of the most important ectoparasites of marine fish, causing ‘white spot disease’ and mass mortality in aquaculture. To accurately predict disease outbreaks and develop prevention strategies, improved detection methods are required that are sensitive, convenient and rapid. In this study, a pair of specific primers based on the C . irritans 18S rRNA gene was developed and used in a real‐time PCR (qPCR) assay. This assay was able to detect five theronts in 1 L of natural seawater. Furthermore, a linear model was established to analyse the log of Ct value and parasite abundance in seawater (y = –2.9623x + 24.2930), and the coefficient of determination (R 2 ) value was 0.979. A lysis buffer was optimized for theront DNA extraction and used for storage sample. This method was superior to the commercial water DNA kit, and there was no significant degradation of DNA at room temperature for 24–96 hr. A dilution method was developed to manage qPCR inhibitors and used to investigate natural seawater samples in a net cage farm with diseased fish, and the findings were consistent with the actual situation. This study provides a valuable tool for assisting in the early monitoring and control of cryptocaryoniasis in aquaculture.

Short-term effect of ambient air pollutant change on the risk of tuberculosis outpatient visits: a time-series study in Fuyang, China - Xin-Qiang Wang; Ying-Qing Li; Cheng-Yang Hu; Kai Huang; Kun Ding; Xiao-Jing Yang; Xin Cheng; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Yong-Zhong Zhang; Zhen-tao Ding; et al. (Environmental Science and Pollution Research, 2022)

Abnormal functional connectivity of the salience network in insomnia - Yongxin Cheng; Ting Xue; Fang Dong; Yiting Hu; Mi Zhou; Xiaojian Li; Ruoyan Huang; Xiaoqi Lu; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2022)

Engineering application of fuzzy evaluation based on comprehensive weight in the selection of geophysical prospecting methods - Maoxin Su; Congcong Li; Yiguo Xue; Peng Wang; Kai Cheng; Yimin Liu (Earth Science Informatics, 2022)

Characterization and genomic analysis of a Demerecviridae phage SP76 with lytic multiple-serotypes of Salmonella - Hui Wang; Yun Shen; Pei LI; Yuyi Xiao; Yanxiu Li; Xiapei Hu; Zhuohao Wang; Zile Cheng; Zitong Wang; Qingxin Liu; Si Qin; Xiang Huo; et al. (Archives of Microbiology, 2022)

Effective Thermal Conductivity Estimation of Fractured Rock Masses - Zheng-Wei Li; Yuan Liu; Shi-Ming Mei; Shi-Cheng Xing; Xiao-Kai Wang (Rock Mechanics and Rock Engineering, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Combining geophysical methods, drilling, and monitoring techniques to investigate carbonaceous shale landslides along a railway line: a case study on Jiheng Railway, China - Maoxin Su; Kai Cheng; Yimin Liu; Yiguo Xue; Peng Wang; Kai Zhang; Congcong Li (Bulletin of Engineering Geology and the Environment, 2021)

Detection method for boulders in subway shield zones based on data fusion multi-resistivity three-dimensional tomography - Maoxin Su; Yimin Liu; Yiguo Xue; Kai Cheng; Fanmeng Kong; Li Guan (Bulletin of Engineering Geology and the Environment, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Short-term waterlogging-induced autophagy in root cells of wheat can inhibit programmed cell death - Li-Lang Zhou; Kai-Yue Gao; Li-Sha Cheng; Yue-Li Wang; Yi-Keng Cheng; Qiu-Tao Xu; Xiang-Yi Deng; Ji-Wei Li; Fang-Zhu Mei; Zhu-Qing Zhou (Protoplasma, 2021)

Heavy Metal Adsorption and Release on Polystyrene Particles at Various Salinities - Beta Susanto Barus; Kai Chen; Minggang Cai; Rongmao Li; Huorong Chen; Cong Li; Jun Wang; Sha-Yen Cheng (Frontiers in Marine Science, 2021)
Microplastics (MPs) and heavy metals are two major types of pollutants that interact with each other, but they are poorly understood. Polystyrene (PS) is one type of MPs that is often detected in aquatic environments. In this study, we examined the adsorption capacity and release rate of heavy metals with respect to different particle sizes of PS, heavy metals, initial heavy metal concentrations, and salinities. Virgin (new) PS with diameters of 20, 50, 130, and 250 μm was used in this study, and four heavy metals (lead, cadmium, copper, and zinc) were used. The results showed that larger PS particle sizes adsorbed more heavy metals even though it took longer to achieve equilibrium adsorption. An increase in heavy metal concentration caused the adsorption capacity (μg g –1 ) of PS particles to also increase, but the adsorption rate (%) decreased. Increased salinity of the heavy metal solution resulted in a slower adsorption time and a lower adsorption capacity and release rate from the surface of PS particles. Different heavy metals also had different adsorption capacities. Pb was consistently more highly adsorbed by MPs, followed by Cu, Zn, and Cd. Larger PS sizes released heavy metals faster than smaller PS sizes, and the amounts of heavy metals released were higher. The heavy metal with the highest release rate was Cd, followed by Pb, Cu, and Zn. Finally, our findings highlight the interactions between PS and heavy metals and strongly support that PS particles can act as vectors for heavy metals in aquatic systems.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Overexpression of TaWRKY14 transcription factor enhances accumulation of chlorogenic acid in Taraxacum antungense Kitag and increases its resistance to powdery mildew - Qun Liu; Wei Zhou; Qinyan Ruan; Haitao Cheng; Tingyao Liu; Leran Wang; Yuan Yuan; Li Li; Jie Wu; Jihong Jiang; Wei Ning; Guoyin Kai (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

A Clipless Pedal-Sensor System for Three Dimensional Kinetic Analysis During Cycling - Kai-Han Liang; Hong-Wen Wu; Li-Cheng Hsieh; Yi-Wen Chang (Journal of Medical and Biological Engineering, 2020)

An A 1 -type granite that borders A 2 -type: insights from the geochemical characteristics of the Zongyang A-type granite in the Lower Yangtze River Belt, China - Xiao-Yan Jiang; Kai Wu; Jin-Cheng Luo; Li-Peng Zhang; Wei Dong Sun; Xiao-Ping Xia (International Geology Review, 2020)

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Effect of miR-27b-5p on apoptosis of human vascular endothelial cells induced by simulated microgravity - Yi-Kai Pan; Cheng-Fei Li; Yuan Gao; Yong-Chun Wang; Xi-Qing Sun (Apoptosis, 2020)
Weightlessness-induced cardiovascular dysfunction can lead to physiological and pathological consequences. It has been shown that spaceflight or simulated microgravity can alter expression profiles of some microRNAs (miRNAs). Here, we attempt to identify the role of miRNAs in human umbilical vein endothelial cells (HUVECs) apoptosis under simulated microgravity. RNA-sequencing and quantitative real-time PCR (qRT-PCR) assays were used to identify differentially expressed miRNAs in HUVECs under simulated microgravity. Then we obtained the target genes of these miRNAs through target analysis software. Moreover, GO and KEGG enrichment analysis were performed. The effects of these miRNAs on HUVECs apoptosis were evaluated by flow cytometry, Western blot and Hoechst staining. Furthermore, we obtained the target gene of miR-27b-5p by luciferase assay, qRT-PCR and Western blot. Finally, we investigated the relationship between this target gene and miR-27b-5p in HUVECs apoptosis under normal gravity or simulated microgravity. We found 29 differentially expressed miRNAs in HUVECs under simulated microgravity. Of them, the expressions of 3 miRNAs were validated by qRT-PCR. We demonstrated that miR-27b-5p affected HUVECs apoptosis by inhibiting zinc fingers and homeoboxes 1 (ZHX1). Our results reported here demonstrate for the first time that simulated microgravity can alter the expression of some miRNAs in HUVECs and miR-27b-5p may protect HUVECs from apoptosis under simulated microgravity by targeting ZHX1.

Land cover patterns in Mongolia and their spatiotemporal changes from 1990 to 2010 - Juanle Wang; Kai Cheng; Qing Liu; Junxiang Zhu; Altansukh Ochir; Davaadorj Davaasuren; Ge Li; Haishuo Wei; Sonomdagva Chonokhuu; Oyunchimeg Namsrai; Ariunsanaa Bat-Erdene (Arabian Journal of Geosciences, 2019)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Autophagy protects HUVECs against ER stress-mediated apoptosis under simulated microgravity - Cheng-Fei Li; Yi-Kai Pan; Yuan Gao; Fei Shi; Yong-Chun Wang; Xi-Qing Sun (Apoptosis, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

A new glycoprotein SPG-8700 isolated from sweet potato with potential anti-cancer activity against colon cancer - Cheng Tian; Meimei Wang; Shanshan Liu; Hang Ma; Kai He; Deqi Zhou; Yanlin Li; Xiaoli Ye; Xuegang Li (Natural Product Research, 2019)

Branched-chain amino acids regulate plant growth by affecting the homeostasis of mineral elements in rice - Cheng Jin; Yangyang Sun; Yuheng Shi; Yuanyuan Zhang; Kai Chen; Yuan Li; Guige Liu; Fang Yao; Deng Cheng; Jie Li; Junjie Zhou; Lianghuan Qu; et al. (Science China Life Sciences, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Variation in Soil Methane Release or Uptake Responses to Biochar Amendment: A Separate Meta-analysis - Cheng Ji; Yaguo Jin; Chen Li; Jie Chen; Delei Kong; Kai Yu; Shuwei Liu; Jianwen Zou (Ecosystems, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

A Neuron-Specific Gene Therapy Relieves Motor Deficits in Pompe Disease Mice - Ni-Chung Lee; Wuh-Liang Hwu; Shin-Ichi Muramatsu; Darin J. Falk; Barry J. Byrne; Chia-Hao Cheng; Nien-Chu Shih; Kai-Ling Chang; Li-Kai Tsai; Yin-Hsiu Chien (Molecular Neurobiology, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

Ammonium, nitrate, and urea play different roles for lipid accumulation in the nervonic acid—producing microalgae Mychonastes afer HSO-3-1 - Cheng Yuan; Kai Xu; Juan Sun; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Ursolic acid activates the TGR5 receptor to enhance GLP-1 secretion in type 1-like diabetic rats - Shih-Hsiang Lo; Yingxiao Li; Kai Chun Cheng; Chiang-Shan Niu; Juei-Tang Cheng; Ho-Shan Niu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

The implication of salience network abnormalities in young male adult smokers - Yangding Li; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yanzhi Bi; Sha Shi; Ting Xue; Xiaoqi Lu; Wei Qin; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Downregulation of miR-221-3p contributes to IL-1β-induced cartilage degradation by directly targeting the SDF1/CXCR4 signaling pathway - Xin Zheng; Feng-chao Zhao; Yong Pang; Dong-ya Li; Sheng-cheng Yao; Shao-song Sun; Kai-jin Guo (Journal of Molecular Medicine, 2017)

Neural correlates of 12-h abstinence-induced craving in young adult smokers: a resting-state study - Yangding Li; Kai Yuan; Yanzhi Bi; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Sha Shi; Xiaoqi Lu; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Frequency characteristics and far-field effect of gravity perturbation before earthquake - Jian-Ke Qiang; Kai Lu; Qian-Jiang Zhang; Kai-Feng Man; Jun-Ying Li; Xian-Cheng Mao; Jian-Qing Lai (Applied Geophysics, 2017)

Functional identification of apple MdJAZ2 in Arabidopsis with reduced JA-sensitivity and increased stress tolerance - Xiu-Hong An; Yu-Jin Hao; En-Mao Li; Kai Xu; Cun-Gang Cheng (Plant Cell Reports, 2017)

Altered resting state functional connectivity of anterior insula in young smokers - Yanzhi Bi; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Yangding Li; Dahua Yu; Wei Qin; Jie Tian (Brain Imaging and Behavior, 2017)

Relationship between molecular weight, monosaccharide composition and immunobiologic activity of Astragalus polysaccharides - Yiping Jiang; Xiaohui Qi; Kai Gao; Wenjun Liu; Na Li; Ningbo Cheng; Gang Ding; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Glycoconjugate Journal, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Polypore diversity in North America with an annotated checklist - Li-Wei Zhou; Karen K. Nakasone; Harold H. Burdsall; James Ginns; Josef Vlasák; Otto Miettinen; Viacheslav Spirin; Tuomo Niemelä; Hai-Sheng Yuan; Shuang-Hui He; Bao-Kai Cui; Jia-Hui Xing; et al. (Mycological Progress, 2016)

Intra-regional and inter-regional abnormalities and cognitive control deficits in young adult smokers - Dan Feng; Kai Yuan; Yangding Li; Chenxi Cai; Junsen Yin; Yanzhi Bi; Jiadong Cheng; Yanyan Guan; Sha Shi; Dahua Yu; Chenwang Jin; Xiaoqi Lu; et al. (Brain Imaging and Behavior, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

The use of food waste-based diets and Napier grass to culture grass carp: growth performance and contaminants contained in cultured fish - Zhang Cheng; Wing-Yin Mo; Xiang-Ping Nie; Kai-Bing Li; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Dynamics of the worldwide number of fungi with emphasis on fungal diversity in China - Yu-Cheng Dai; Bao-Kai Cui; Jing Si; Shuang-Hui He; Kevin D. Hyde; Hai-Sheng Yuan; Xiao-Yong Liu; Li-Wei Zhou (Mycological Progress, 2015)

Co-transplantation of Hematopoietic Stem Cells and Cxcr4 Gene-Transduced Mesenchymal Stem Cells Promotes Hematopoiesis - Wei Chen; Miao Li; Guizhen Su; Yu Zang; Zhiling Yan; Hai Cheng; Bin Pan; Jiang Cao; Qingyun Wu; Kai Zhao; Feng Zhu; Lingyu Zeng; et al. (Cell Biochemistry and Biophysics, 2015)

Late Permian–Triassic siliciclastic provenance, palaeogeography, and crustal growth of the Songpan terrane, eastern Tibetan Plateau: evidence from U–Pb ages, trace elements, and Hf isotopes of detrital zircons - Yu-Xiu Zhang; Lu Zeng; Zhi-Wu Li; Cheng-Shan Wang; Kai-Jun Zhang; Wen-Guang Yang; Tong-Lou Guo (International Geology Review, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Mouse organ coefficient and abnormal sperm rate analysis with exposure to tap water and source water in Nanjing reach of Yangtze River - Rongfei Zhang; Liujun Zhang; Dongsheng Jiang; Kai Zheng; Yibin Cui; Mei Li; Bing Wu; Shupei Cheng (Ecotoxicology, 2014)

The significance of YKL-40 protein in liver fibrosis - Hui Tao; Jing-Jing Yang; Kai-Hu Shi; Cheng Huang; Lei Zhang; Xiong-Wen Lv; Jun Li (Inflammation Research, 2014)

Late Palaeozoic and early Mesozoic tectonic and palaeogeographic evolution of central China: evidence from U–Pb and Lu–Hf isotope systematics of detrital zircons from the western Qinling region - Yu-Xiu Zhang; Lu Zeng; Kai-Jun Zhang; Zhi-Wu Li; Cheng-Shan Wang; Tong-Lou Guo (International Geology Review, 2014)

Taxonomy and phylogeny of Ceriporia (Polyporales, Basidiomycota) with an emphasis of Chinese collections - Bi-Si Jia; Li-Wei Zhou; Bao-Kai Cui; Bernard Rivoire; Yu-Cheng Dai (Mycological Progress, 2014)

HOXA9 Gene Expression in Acute Myeloid Leukemia - De-Peng Li; Zhen-Yu Li; Wei Sang; Hai Cheng; Xiu-Ying Pan; Kai-Lin Xu (Cell Biochemistry and Biophysics, 2013)

Simultaneous removal of cadmium and sulfamethoxazole from aqueous solution by rice straw biochar - Xuan Han; Cheng-feng Liang; Ting-qiang Li; Kai Wang; Hua-gang Huang; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Arsenic contamination in the freshwater fish ponds of Pearl River Delta: bioaccumulation and health risk assessment - Zhang Cheng; Kun-Ci Chen; Kai-Bin Li; Xiang-Ping Nie; Sheng Chun Wu; Chris Kong-Chu Wong; Ming-Hung Wong (Environmental Science and Pollution Research, 2013)

Saccharopolyspora dendranthemae sp. nov. a halotolerant endophytic actinomycete isolated from a coastal salt marsh plant in Jiangsu, China - Yue-Ji Zhang; Wen-Di Zhang; Sheng Qin; Guang-Kai Bian; Ke Xing; Yun-Feng Li; Cheng-Liang Cao; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2013)

Regulation of Neural Stem Cell Differentiation by Transcription Factors HNF4-1 and MAZ-1 - Jiao Wang; Hua Cheng; Xiao Li; Wei Lu; Kai Wang; Tieqiao Wen (Molecular Neurobiology, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Effect of Low-Intensity Pulsed Ultrasound on MMP-13 and MAPKs Signaling Pathway in Rabbit Knee Osteoarthritis - Xueping Li; Jianan Li; Kai Cheng; Qiang Lin; Daxin Wang; Hongfei Zhang; Hengyuan An; Mingxia Gao; Anliang Chen (Cell Biochemistry and Biophysics, 2011)

Mercury Biomagnification in the Aquaculture Pond Ecosystem in the Pearl River Delta - Zhang Cheng; Peng Liang; Ding-Ding Shao; Sheng-Chun Wu; Xiang-Ping Nie; Kun-Ci Chen; Kai-Bin Li; Ming-Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Adenovirus-mediated delivery of shRNA against bFGF mRNA suppresses growth of cultured human primary prostatic stromal cells - Kai Wang; Linfeng Cheng; Yinghong Liang; Donghui Liu; Kai Li; Ping Wang (Molecular Biology Reports, 2011)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)